2021
DOI: 10.3906/sag-2105-177
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate turbulence measurements in patients with dipper and non-dipper hypertension: the effects of autonomic functions

Abstract: Background/aim: Hypertensive patients have shown autonomic dysfunction that is closely associated with the measurements of heart rate variability (HRV) and heart rate turbulence (HRT). We aimed to show the alterations of HRV and HRT measurements in patients with both dipper and non-dipper hypertension. Materials and methods:This was a retrospective study consisting of one hundred and twenty-three participants (Mean age ±SD), 55.7 ±14.8 years; range, 18-90 years ) .The participants were divided into two groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, there is no previous study comparing MS and time-domain HRV parameters in the literature. Disruption of the dipping pattern is known to be associated with a reduction in pNN50 and rMSSD [28]. In our study, we found that the vagal activity markers pNN50 and rMSSD supported frequency domain analysis and were associated with MS. Also, there was an independent association between pNN50 and rMSSD, and MS.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To the best of our knowledge, there is no previous study comparing MS and time-domain HRV parameters in the literature. Disruption of the dipping pattern is known to be associated with a reduction in pNN50 and rMSSD [28]. In our study, we found that the vagal activity markers pNN50 and rMSSD supported frequency domain analysis and were associated with MS. Also, there was an independent association between pNN50 and rMSSD, and MS.…”
Section: Discussionsupporting
confidence: 76%
“…To the best of our knowledge, there is no previous study comparing MS and time-domain HRV parameters in the literature. Disruption of the dipping pattern is known to be associated with a reduction in pNN50 and rMSSD [28].…”
Section: Discussionmentioning
confidence: 99%
“…The autonomic equilibrium swings toward the sympathetic nervous system at night, which is believed to be the primary mechanism for non-dipper hypertension. In non-dipper hypertensive patients, ventricular repolarization heterogeneity and cardiac conduction disruption were found at higher frequencies [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The 24-h blood pressure variability curve was mostly presented in a dipper type, that is, "two peaks and one valley." 3 In contrast, non-dipper blood pressure is a circadian rhythm abnormality in hypertensive patients, defined as a decrease in blood pressure of <10% at night or >20% of the daytime blood pressure. 4 Patients with non-dipper hypertension (NDH) have higher risks of target organ damage such as left ventricular hypertrophy, carotid atherosclerosis, and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a common chronic disease of the cardiovascular system, characterized by increased blood pressure in the arteries and elevated peripheral vascular resistance, which can increase the heart's systolic afterload, leading to structural and functional damage to relevant organs 1,2 . The 24‐h blood pressure variability curve was mostly presented in a dipper type, that is, “two peaks and one valley.” 3 In contrast, non‐dipper blood pressure is a circadian rhythm abnormality in hypertensive patients, defined as a decrease in blood pressure of <10% at night or >20% of the daytime blood pressure 4 . Patients with non‐dipper hypertension (NDH) have higher risks of target organ damage such as left ventricular hypertrophy, carotid atherosclerosis, and stroke 5 .…”
Section: Introductionmentioning
confidence: 99%